Outsourcing Agreement In The Perspective Of Pancasila Industrial Relations - Rizal Anugrah Bachriar (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
In the midst of the rebirth of public concern over the dangers of capitalism, the government would legalize the practice of outsourcing that are economically and morally detrimental to workers / laborers. Outsourcing is an agreement made between employers and workers / laborers, which the company can transfer part of its work to other companies through chartering agreement / service provider's written work. The outsourcing company usually makes a contractual agreement with the workers if there are companies that need workers. The contract is usually only valid for jobs are still available, and if the contract for the work has expired, then the working relationship between workers and outsourcing company also ended. Key Words: Outsourcing; Pancasila; Employment Act.